ISRÂ’ÎLÎYÂT DALAM KITAB ḤÂSHIYAH AL-ṢÂWÎ ‘ALÂ TAFSÎR JALÂLAYN KARYA AḤMAD AL-ṢÂWÎ - Mahfud, Hakim (Jurnal Studi Ilmu-ilmu Al-Qur’an dan Hadis, 2019)
Al-ṣâwî’s attitude toward Isrâ’îlîyât history (attitude in the book of ḥâshiyah) is reflected in his collection of such histories. In many interpretations, Isrâ’îlîyât’s history is widely cited, but the quotation does not include any evidence of the truth of the story, nor the quality of the history. In this article, the author examines al-ṣâwî’s attitude toward the Isrâ’îlîyât story contained in ḥâshiyah al-ṣâwî’s alâ Tafsîr Jalâlayn. This study aimed to find out whether al-Sawi was critical of the Israeli story. The author uses the library reseach method (literature). To obtain information from various sources, the author uses the documentation method then analyzes the data using a discourse analysis method developed by Tuen A.van Djijk namely macro structure, superstructure, and microstructure. The results of this study reveal that al-Sawi does not always provide comments on the quoted Isra’iliyat story. There are several stories that he included in his sanad and gave an explanation of the truth of its history. He also does not display sanad from the history cited. Likewise with the history of the record, sometimes al-Sawi comments, but also the opposite. Keyword: Israiliyyat, attitude of al-ṣâwî, and ḥâshiyah al-ṣâwî